engaruh Indeks Dow Jones, Nikkei 225, Kospi, dan Shanghai Composite Index terhadap Indeks Harga Saham Gabungan Bursa Efek Indonesia Periode Tahun 2004 -2008 - Deitiana, Tita; Stella, Stella (Bina Nusantara University, 2009)
The Jakarta Composite Index has been positively growing for last six years. As we know, the globalization is already happening in the financial sector and strong relationships have developed between the global stock markets all around the world. This research was intended to know and analyze the simultaneous and partial effect of the global stock index to Jakarta Composite Index. The Global Stock Index is represented by four regional indexes, namely Dow Jones, Nikkei 225, KOSPI, and Shanghai Composite Index. The research method used is multiple regression analysis used to find out the effect of independent variables to dependent variable. The data was the weekly closing price of Dow Jones, Nikkei 225, KOSPI, and Shanghai Composite Index as independent variables and the Jakarta Composite Index as a dependent variable from year 2004 to 2008. Results indicate that simultaneously and partially the Dow Jones, Nikkei 225, KOSPI, and Shanghai Composite Index affected the Jakarta composite index. This result shows that recently the movement of the Jakarta Composite Index is being influenced by the movement of global stock index.